A new technique for the confinement of rectangular cross section reinforced concrete columns - Janwaen, Worajak (2017)
In this work a new technique aiming an efficient confinement of reinforced concrete (RC) columns of rectangular cross-section is presented. This technique is based on the concept of applying strips of carbon fiber reinforced polymer (CFRP) wet layup sheets with a certain pre-stress level. A mechanical system was developed for pre-stressing the CFRP strips. The experimental program was composed by the following four types of RC column elements, all of cross section aspect ratio (larger to smaller edge ratio) of 2.0: 1) reference column without any confinement; 2) RC column fully wrapped with CFRP; 3) RC column confined with strips of CFRP; 4) RC column confined according to the new proposed technique. The columns have a cross section of 120×240 mm2, height of 700 mm, and corner radius of 25 mm. All columns were subjected to axial compressive loading until their failures. The experimental results showed that the new proposed technique provides a significant increase of the load carrying capacity compared to the conventional strengthening techniques and the reference columns. Based on the obtained experimental results, the new proposed technique remarkably increased the confinement effectiveness of the rectangular RC columns.